Analysis of the Efficiency of Solar Power Plants as an Alternative Energy Source CCTV Integrated with Smartphones - Dimas Yudho Wibowo; Dino Erivianto; Rahmaniar Rahmaniar (Universitas Medan Area, 2025)
Solar energy is one of the renewable energies which is an alternative energy for producing electrical energy. The first research stage involves conducting literature studies and field observations related to the problem to be researched. Next, collect the data needed to plan an off-grid solar power plant at the Medan City Study House. This PLTS is also capable of being an alternative energy source for CCTV which is capable of supplying electrical energy for 24 hours. Where CCTV plays a very important role in the Medan City Study House as the security system used. PLTS is highly recommended to be implemented in densely populated areas because PLTS has very minimal emissions and is environmentally friendly. The cost of energy (COE) / kWh from this PLTS is 0.073/kWh. Meanwhile, the price per kWh from PLN is 0.089/kWh. Solar panels produce 6,694 kWh of energy per year. The energy produced by solar panels is sufficient to supply load needs which only require 153,300 kWh of energy per year.